STRATEGIES OF LOCAL SUSTAINABLE DEVELOPMENT IN THE REGION OF AP VOJVODINA - PARTICIPATION OF YOUNG PEOPLE IN CREATING STRATEGIES - Glišin, Vanja; Stančetić, Veran; Matković, Aleksandar (Political Review, 2024)
The key issue of this paper is the scope of municipalities and cities of AP Vojvodina in the participation of citizens when planning local sustainable development. To find an answer to this question, the importance of sustainable development is explained first, its local dimension next, as well as the necessity of citizen participation (electronic and traditional). Then, a "surface" segment of the analysis was performed – the state of local strategies in the APV area (their existence and public availability) is analyzed, ie the tendency of municipalities and cities of Vojvodina towards strategic management and sustainable development. The second segment of the analysis is deepened, focusing on the real involvement of citizens in the creation and implementation of local development documents, with a special focus on young people (15–25 years of age) and their views on these issues. The paper presents the research findings, i.e. the perception of young people when it comes to involvement in local affairs, sustainable development, and participation in general. Although we live in an information age in which there are technological, but also formal and legal conditions for citizen participation, it is still assessed as insufficient. Therefore, the paper elaborates on the reasons for this situation and offers guidelines for improving this area. Primary and secondary sources were used in the paper. By analyzing the documents, we obtained data related to the research subject. It is primarily a qualitative analysis of primary data sources, but also an analysis of domestic and foreign relevant literature. Along with empirical research, an analysis of existing studies in this area was performed. Therefore, the method of analysis (descriptive and explanatory analysis) and the method of synthesis were used, to understand the complex whole based on the described and explained basic concepts and processes.